ANALISIS KINERJA KEUANGAN PT. KIMIA FARMA (PERSERO) TBK YANG TERDAFTAR DI BURSA EFEK INDONESIA - Tasya Sitompul; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study aims to determine the financial performance of PT. Kimia Farma (Persero) Tbk, which was listed on the Indonesia Stock Exchange in the 2014-2018 period measured using financial ratio standards. Data analysis uses the time series analysis method, which compares between time or between periods with the aim to be seen graphically. Data and information obtained from the website of PT. Kimia Farma (Persero) Tbk. From the results of data analysis research (1) Analysis of Liquidity Ratio with indicators Current Ratio, Quick Ratio and Cash Ratio in the category of not good and are on Iliquid (2) Analysis of Solvency Ratio with indicators Debt To Assets Ratio and Debt To Equity Ratio experiencing fluctuating conditions Overliquid conditions and in the unfavorable category (3) Analysis of Profitability Ratios with indicators of Gross Profit Margin (GPM), Net Profit Margin (NPM), Return On Investment (ROI) and Return On Equity (ROE) in categories below industry standards and in Iliquid conditions (ROI) 4) Analysis of Activity Ratio with indicators of Inventory Turnover, Working Capital Turnover, Total Asset Turnover has fluctuated and is in the unfavorable category and in Iliquid conditions.Keywords: Analysis, Liquidity, Solvency, Profitability, Activity.